Pemanfaatan Sampah Organik sebagai Pupuk Kompos untuk Meningkatkan Produktivitas Pertanian di Desa Semare Kecamatan Kraton Kabupaten Pasuruan - Zuhri, Zainullah; Sari, Mayang; Ulya, Fahimatul; Hendratama, Handik; Fathurrohman, Amang (Humanist Journal, 2024)
The program of utilizing organic waste as compost to improve agricultural productivity in Semare Village aims to reduce dependency on chemical fertilizers by utilizing organic waste as an environmentally friendly fertilizer. This program involves the local community in waste segregation and composting training, which can be used to improve soil quality and agricultural yields. Despite facing challenges such as limited infrastructure and resources, this program successfully raised environmental awareness, empowered the community, and improved agricultural productivity sustainably. With active community participation, the program has the potential to reduce waste in Semare Village and create new economic opportunities.